Functional movement disorders are not uncommon in the elderly. Issue 4 (15th February 2013) - Batla, Amit; Stamelou, Maria; Edwards, Mark J.; Pareés, Isabel; Saifee, Tabish A.; Fox, Zoe; Bhatia, Kailash P.
ABSTRACT Background Functional movement disorders (FMDs) are thought to be rare in the elderly. Clinical characteristics of the elderly people who develop FMDs are rarely reported. The objective of this study was to highlight the clinical characteristics of FMD in the elderly and compared these with a cohort of patients with a younger age of onset. Methods The authors performed a retrospective review of the clinical records of patients with FMD who were seen at their center in the last 5 years and had consented to be included in research studies. Patients fulfilling currently accepted diagnostic criteria for FMD as documented, clinically established, or probable were included. Results Of 151 patients with FMD who were identified and had sufficient information, 21.0% (n=33) had an onset after age 60 years (elderly group). The mean age of onset of FMD was 63.5 years (standard deviation, 5.2 years) in the elderly group and 35.5 years (standard deviation, 12.6 years) in the younger group. Tremor was the most common movement disorder in both groups (elderly group, 33.3%; younger group: 38.9%). Fixed dystonia was not observed in any patient who had an FMD onset after age 60 years. Gait abnormalities were significantly more common in the elderly group (69.7%) than in younger patients (23.5%; P<0.001). Associated psychogenic nonepileptic seizures tended to be more common in elderly patients (18.2%) compared with younger patients (13%; P=0.06). Conclusions Contrary to common perceptions, FMDs are not uncommon in the elderly, and 1 in 5 patients in the current cohort, onset of FMD occurred after age 60 years. Gait abnormalities and psychogenic nonepileptic seizures may be more common in older patients. © 2013 Movement Disorder Society